The apical conjugate efflux pump ABCC2 (MRP2) - Nies, Anne; Keppler, Dietrich (Pflügers Archiv, 2007)
ABCC2 is a member of the multidrug resistance protein subfamily localized exclusively to the apical membrane domain of polarized cells, such as hepatocytes, renal proximal tubule epithelia, and intestinal epithelia. This localization supports the function of ABCC2 in the terminal excretion and detoxification of endogenous and xenobiotic organic anions, particularly in the unidirectional efflux of substances conjugated with glutathione, glucuronate, or sulfate, as exemplified by leukotriene C4, bilirubin glucuronosides, and some steroid sulfates. The hepatic ABCC2 pump contributes to the driving forces of bile flow. Acquired or hereditary deficiency of ABCC2, the latter known as Dubin-Johnson syndrome in humans, causes an increased concentration of bilirubin glucuronosides in blood because of their efflux from hepatocytes via the basolateral ABCC3, which compensates for the deficiency in ABCC2-mediated apical efflux. In this article we provide an overview on the molecular characteristics of ABCC2 and its expression in various tissues and species. We discuss the transcriptional and posttranscriptional regulation of ABCC2 and review approaches to the functional analysis providing information on its substrate specificity. A comprehensive list of sequence variants in the human ABCC2 gene summarizes predicted and proven functional consequences, including variants leading to Dubin-Johnson syndrome.
Published online: 18 July 2006
Gesehen am 18.02.2021